Exploring visitation at rivers to understand drowning risk. Issue 5 (6th June 2018) - Peden, Amy E; Franklin, Richard C; Leggat, Peter A
Abstract : Introduction: Globally, rivers are a common drowning location. In Australia, rivers are the leading location for fatal drowning. Limited information exists on exposure and impact on river drowning risk. Methods: Australian unintentional fatal river drowning data (sourced from coronial records) and nationally representative survey data on river visitation were used to estimate river drowning risk based on exposure for adults (18 years and older). Differences in river drowning rates per 100 000 (population and exposed population) were examined by sex, age group, activity prior to drowning, alcohol presence and watercraft usage. Results: Between 1 January 2014 and 31 December 2016, 151 people drowned in Australian rivers; 86% male and 40% aged 18–34 years. Of survey respondents, 73% had visited a river within the last 12 months. After adjusting for exposure: males were 7.6 times more likely to drown at rivers; female drowning rate increased by 50% (0.06–0.09 per 100 000); males aged 75+ years and females aged 55–74 years were at highest risk of river drowning; and swimming and recreating pose a high risk to both males and females. After adjusting for exposure, males were more likely to drown with alcohol present (RR=8.5; 95% CI 2.6 to 27.4) and in a watercraft-related incident (RR=25.5; 95% CI 3.5 to 186.9). Conclusions: Calculating exposure for river drowning is challenging due to diverse usage, time spent and number of visits. While males were more likely to drown, the differences between males and females narrow after adjusting for exposure. This is an important factor to consider when designing and implementing drowning prevention strategies to effectively target those at risk.